KOMPETENSI PEDAGOGIK TUTOR DALAM PENDIDIKAN KESETARAAN DI PKBM KAK SETO KELURAHAN SUKAMAJU KECAMATAN SAIL KOTA PEKANBARU PROVINSI RIAU - Rachmadani, Annisa Suci; Maemunaty, Titi; Wilson, Wilson (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The problem in this research is how competence is the pedagogical tutor in equality education at PKBM kak seto-kelurahan sukamaju sail city of pekanbaru province riau? The value of this research is theoretically: (1) improving the concept of learning in equality education. (2) improve the pedagogical competence of teachers in equality education. (3) enhancing students’ abilities in equality education. And are practically: (1) PKBM managers, for information in terms of developing and developing educators through learning in equality eaducation. (2) tutors, for input materials to know a good and effective way to manage samentary education learning. (3) studenst, as an input ingredient to can plant knowledge about e learning education equality. (4) researchers, for input materials to expand the understanding and application of advanced teoni on the college bench on equality education. The study is descriptive with the subject’s qualitative approach to this study is 5 people, the removal of the research subject in the research using the intrinsishe sampling instrument that was used as a guideline for the 94 interviews. The pedagogic competence tutor in the equality education at PKBM kak seto-kelurahan sukamaju sail city of pekanbaru province riau can be explained by indicators (1) developing the curiculum and designing learning, (2) ruling theories and principles of learning, (3) organizing the curriculum and designing learning, (4) organizing special intructional purposes (TIK) for the benefit of learning, (5) communicating effectively, emphatically, and a unit with leaners, (6) administer evaluations and assessments for the sake of learning. The result of the study are known that the pedagogical tutor at PKBM kak seto-san has fended there in the main event of organizing the study and conducting the evaluation. The meaning is the pedagogic competence of tutors abilities of tutors in performing learning.Key Words: Competence, Pedagogical